2018
DOI: 10.1037/bne0000239
|View full text |Cite
|
Sign up to set email alerts
|

Early adolescent adversity inflates threat estimation in females and promotes alcohol use initiation in both sexes.

Abstract: Childhood adversity is associated with exaggerated threat processing and earlier alcohol use initiation. Conclusive links remain elusive, as childhood adversity typically co-occurs with detrimental socioeconomic factors, and its impact is likely moderated by biological sex. To unravel the complex relationships among childhood adversity, sex, threat estimation, and alcohol use initiation, we exposed female and male Long-Evans rats to early adolescent adversity (EAA). In adulthood, >50 days following the last ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 70 publications
(110 reference statements)
7
25
0
Order By: Relevance
“…Previous experiments related to aversive prediction error signalling using rodents have been conducted using only males (Assareh et al., ; Cole & McNally, ; Groessl et al., ; Johansen et al., ; McNally & Cole, ; Ozawa et al., ), and one study in humans used both males and females but did not consider sex as a factor in their analyses (Roy et al., ). Sex differences in baseline behaviour (i.e., nose poke rate and absolute fear levels) in the optogenetics results are consistent with previous findings in the same behavioural task (Walker et al., ). While the effect of optogenetic inhibition to decrease fear to uncertainty was observed across sexes, subtle interactions with sex and the pattern of fear to uncertainty and safety were observed.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Previous experiments related to aversive prediction error signalling using rodents have been conducted using only males (Assareh et al., ; Cole & McNally, ; Groessl et al., ; Johansen et al., ; McNally & Cole, ; Ozawa et al., ), and one study in humans used both males and females but did not consider sex as a factor in their analyses (Roy et al., ). Sex differences in baseline behaviour (i.e., nose poke rate and absolute fear levels) in the optogenetics results are consistent with previous findings in the same behavioural task (Walker et al., ). While the effect of optogenetic inhibition to decrease fear to uncertainty was observed across sexes, subtle interactions with sex and the pattern of fear to uncertainty and safety were observed.…”
Section: Discussionsupporting
confidence: 91%
“…In the procedure, three auditory cues predict unique foot shock probabilities: danger ( p = 1.00), uncertainty ( p = .375) and safety ( p = .00). Using conditioned suppression of rewarded nose poking as our dependent measure, we have previously found excellent discriminative fear in male and female rats: high to danger, intermediate to uncertainty, and low to safety (Berg et al., ; DiLeo, Wright, & McDannald, ; Ray, Hanlon, & McDannald, ; Walker et al., ; Wright et al., ). Theoretically, +PEs provide an updating mechanism that would permit fear to uncertainty to remain at an intermediate level.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have reported sex differences in danger-safety discrimination (Day et al, 2016;Foilb et al, 2018;Greiner et al, 2019). We find only modest sex differences in our fear procedure (Walker et al, 2018;Walker et al, 2019), suggesting similar neural circuits may be utilized across sexes. Of course, females and males may achieve similar performance through differing neural mechanisms.…”
Section: Discussionsupporting
confidence: 51%